(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
Adsorption and catalytic properties of sensor materials based on SnO2 promoted by 3-d metals (Co, Fe, Ni, Cu) are investigated. Maximal products desorption temperatures for all catalysts on a few tens of degrees are lower than total-lot conversion temperatures of reagents for H2 and CO oxidation reaction. It is to be evidence that under catalysis desorption step is not limited.